Social Support, Religiosity, and Parenting Stress in Mothers of Children with Special Needs - Rahayu, Aina; Mariyati, Lely Ika (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the relationship between social support, religiosity, and parenting stress among mothers of children with special needs. Utilizing Likert scale-based psychological assessments, data were collected from 30 mothers at Mi Nurul Islam Mojokerto. The analysis revealed significant correlations between social support, religiosity, and parenting stress, suggesting that higher levels of social support and religiosity were associated with reduced parenting stress among these mothers. This study underscores the importance of considering both social support and religiosity as potential factors in mitigating parenting stress among mothers of children with special needs, thus emphasizing the need for tailored interventions to support this vulnerable population Highlights : The study investigates the relationship between social support, religiosity, and parenting stress among mothers of children with special needs. Data from 30 mothers at Mi Nurul Islam Mojokerto were collected and analyzed using Likert scale-based psychological assessments. Higher levels of social support and religiosity were found to be associated with reduced parenting stress, underscoring the importance of tailored interventions for this vulnerable population. Keywords: Parenting stress, Social support, Religiosity, Special needs children, Psychological scales